Resveratrol Preconditioning Induces a Novel Extended Window of Ischemic Tolerance in the Mouse Brain. Issue 8 (August 2015) - Koronowski, Kevin B.; Dave, Kunjan R.; Saul, Isabel; Camarena, Vladimir; Thompson, John W.; Neumann, Jake T.; Young, Juan I.; Perez-Pinzon, Miguel A.
<x xml:space="preserve">Abstract</x> Background and Purpose— Prophylactic treatments that afford neuroprotection against stroke may emerge from the field of preconditioning. Resveratrol mimics ischemic preconditioning, reducing ischemic brain injury when administered 2 days before global ischemia in rats. This protection is linked to silent information regulator 2 homologue 1 (Sirt1) and enhanced mitochondrial function possibly through its repression of uncoupling protein 2. Brain-derived neurotrophic factor (BDNF) is another neuroprotective protein associated with Sirt1. In this study, we sought to identify the conditions of resveratrol preconditioning (RPC) that most robustly induce neuroprotection against focal ischemia in mice. Methods— We tested 4 different RPC paradigms against a middle cerebral artery occlusion model of stroke. Infarct volume and neurological score were calculated 24 hours after middle cerebral artery occlusion. Sirt1-chromatin binding was evaluated by ChIP-qPCR. Percoll gradients were used to isolate synaptic fractions, and changes in protein expression were determined via Western blot analysis. BDNF concentration was measured using a BDNF-specific ELISA assay. Results— Although repetitive RPC induced neuroprotection from middle cerebral artery occlusion, strikingly one application of RPC 14 days before middle cerebral artery occlusion showed the most robust protection, reducing infarct volume by 33% and improving neurological score by 28%. Fourteen days after RPC, Sirt1 protein was increased 1.5-fold and differentially bound to the uncoupling protein 2 and BDNF promoter regions. Accordingly, synaptic uncoupling protein 2 level decreased by 23% and cortical BDNF concentration increased 26%. Conclusions— RPC induces a novel extended window of ischemic tolerance in the brain that lasts for at least 14 days. Our data suggest that this tolerance may be mediated by Sirt1 through upregulation of BDNF and downregulation of uncoupling protein 2.